Aplikasi Peramalan Jumlah Siswa Sekolah Dasar di Kabupaten Tanah Laut Menggunakan Metode Holtâs Double Exponential Smoothing - Apriliyani, Nora; Rhomadhona, Herfia; Permadi, Jaka (Fakultas Teknik Universitas Maritim Raja Ali Haji, 2018)
Learning processes in the elementary schools at Tanah Laut District is affected by the number of students. Through the number of students can be predicted how much the need of additional teachers, rooms, textbooks and learning medias that support learning processes in the schools. In other words, the infrastructure of the schools can be predicted by the number of students that is registered in Tanah Laut District. The research use Holtâs Double Exponential Smoothing method to predicting the number of the prospective students in Tanah Laut District. Mean Absolute Percentage Error (MAPE) technique is used to calculate the percentage of error from the forecastingâs result. The system is designed by Entity Relationship Diagram (ERD) and Data Flow Diagram (DFD). The forecasting that have been done said that the number of Tanah Lautâs elementary school students at 2018 is 35655 students, with the value of MAPE is about 0.77%, Î± = 0.77 and Î² = 0.8.